Rock Avalanche-Generated Sediment Mass Flows: Definitions and Hazard - Mitchell, Andrew; McDougall, Scott; Aaron, Jordan; Brideau, Marc-André (Frontiers in Earth Science, 2020)
Rock avalanches can trigger destructive associated hazards following the initial collapse and fragmentation of a rock slope failure. One of these associated hazards occurs when the material derived from the initial collapse of the source zone impacts and mobilizes a mass flow composed of sediment from along the travel path. These mass flows can be grouped into radial impact areas that occur on relatively flat, open terrain (typically a floodplain), and more linear impact areas that occur in channelized terrain. Rock avalanche-generated sediment mass flows are an important consideration because they can significantly increase the area impacted by an event, thereby increasing the hazard area, especially in valley bottoms where there are likely more elements at risk. Existing runout prediction methods do not consistently account for the increase in the impact area from rock avalanche-generated sediment mass flows. Thus, there is a need for a simple data-supported method for estimating the extent of mass flow impacts resulting from an initial rock avalanche event with sediments along the potential travel path. This paper presents data from 32 rock avalanches and 23 rock avalanche-generated sediment mass flows from around the world, described using a consistent set of quantitative and qualitative attributes. A wide range of mass flow impacts were observed, with the sediment mass flow impact area or runout length exceeding the impact of the coarse, rocky debris in some cases. The area and length impacted by the coarse, rocky debris is estimated using multiple linear regressions considering the event volume and topographic features. The sediment mass flow dataset is used as input to develop an exponential distribution of the area or runout length of the sediment mass flow over that of the coarse, rocky debris. A decision tree framework is presented for estimating the extent of potential rock avalanches and potential rock avalanche-generated sediment mass flows for hazard and risk analysis, which is demonstrated by comparing the stochastic empirical predictions to those from numerical runout modelling.